The construction and deconstruction of "spectacular" subjectivities : a study of the instagram assemblage - Kollyri, Lydia (My University, 2022)
Instagram has succeeded in becoming a pervasive part of everyday life for many of its million users. Although some researchers tend to overlook its significance, as noted by Abidin (2016a), we should not turn our back on things that may seem trivial or “superficial”, as the familiar is not necessarily understood (Hegel, 1807/1977). Drawing on the Debordian concept of the spectacle, the Foucauldian approach of power and principles of Actor Network Theory, this doctoral dissertation investigates the Instagram platform as a sociotechnical assemblage of heterogeneous human and non-human actors exploring the power relations articulated on it. For that purpose, three empirical studies have been conducted focusing on different entities of the Instagram assemblage, namely i) the platform’s structural elements, such as affordances and algorithms, ii) discourses on Instagram and iii) Instagram users, exploring the following master research questions: Which is the ideal use of the Instagram platform? How does Instagram function as a norm-(re)producing mechanism and how it constructs user subjectivities? What power mechanisms does Instagram employ? How do users react to these mechanisms? The first study employs an interface analysis investigating the Instagram ideal use and inscribed subjectivities, focusing on the platform's interfaces together with the surrounding Instagram discourses. The findings show that four types of “ideal” users are prescribed. The second study focuses on the Instagram algorithms as a recommendation system exploring whether a filter bubble emerges. Applying the algorithmic auditing method, I have shown that Instagram algorithms render certain topics much more salient, generating a filter bubble of commercial and soft topics. Both studies’ results indicate that Instagram closely resembles a contemporary spectacle, revolving around the aestheticization of everyday life with various repercussions. Based on the results of the previous studies, in the third study, 15 in-depth interviews have been conducted with Instagram “ordinary” users to explore how they react to Instagram power mechanisms. The results show that individuals adopt different using positions, following, negotiating, opposing and subverting the system. Taking everything into account, this dissertation concludes by utilizing de Certeau’s approach regarding place and space to analyze the platforms’ ecosystem and revealing the strategies constructing the Instagram place, and the tactics transforming it into a space. In the conclusion section, the notions of voyeur and walker are brought to attention, while the notion of transient is introduced, contributing to the conceptualization of user agency. The findings of this doctoral research can be used to inform the design of tools that can strengthen users’ agency as well as provide directions on how users’ relationships with the platforms can meliorate.
Keywords: critical internet studies; Instagram subjectivities; Instagram algorithms; Instagram spectacle; user agency; power relations